Long-term economc burden and related influencing factors of pediatric cataracst: A population-based study in South Korea - Semin Jang; Sang Jun Park; Seo Yoon Choi; Migyeong Jeong; Siin Kim; Hae Sun Suh (PLoS ONE, 2025)
Pediatric cataracts are a significant cause of childhood blindness, requiring long-term management. This study evaluated the economic burden of pediatric cataract surgery in South Korea and identified factors influencing the medical costs, particularly in patients with complications after cataract surgery. We used National Health Insurance Service claims data, covering the Korean population, including pediatric patients (aged ≤5 years) who underwent cataract surgery between 2004 and 2011. We measured healthcare resource utilization (outpatient, inpatient, and emergency department visits) and cataract-related medical costs over an 8-year follow-up after cataract surgery. We further explored factors influencing medical costs using a generalized linear model. A total of 1297 pediatric patients (mean age: 2.2 years, 56.8% male) were included. Over 8 years, patients had an average of 30 outpatient visits, 2.7 inpatient visits, and 3 emergency department visits. The total average medical cost over 8 years was $2,391 per patient, with significantly higher costs in those developed retinal detachment ($7729) or glaucoma ($8,821) developed after the surgery. Additionally, higher costs were associated with older age at surgery, higher income, the presence of postoperative complications, and multiple surgeries. Pediatric cataract surgery resulted in a considerable long-term economic burden, particularly when accompanied by postoperative complications. This study provides real-world evidence underscoring the need for improvement in pediatric cataract management to ensure optimal care for young patients at risk of vision impairment.